2010
DOI: 10.1002/bjs.7001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term benefit and cost-effectiveness analysis of screening for abdominal aortic aneurysms from a randomized controlled trial

Abstract: The mortality benefit of screening for AAA in men aged 64-73 years was maintained in the longer term and screening was cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
118
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 33 publications
4
118
1
3
Order By: Relevance
“…57 Since that review, a number of further modelling studies have been published drawing on data from a variety of sources: for example studies relating to Italy, 15 to the Netherlands and Norway, 58 to Canada 59,60 and to Denmark. 61 These have all concluded that screening is acceptably cost-effective, with the exception of a study using data from Denmark and other sources, which concluded that screening did not seem to be cost-effective. 62 A recent modelling study, again using Danish data, contradicts that previous conclusion, suggesting that screening men at age 65 years is highly cost-effective compared with no screening and, additionally, that rescreening after 5 years may be a cost-effective extension to the programme.…”
Section: Introductionmentioning
confidence: 99%
“…57 Since that review, a number of further modelling studies have been published drawing on data from a variety of sources: for example studies relating to Italy, 15 to the Netherlands and Norway, 58 to Canada 59,60 and to Denmark. 61 These have all concluded that screening is acceptably cost-effective, with the exception of a study using data from Denmark and other sources, which concluded that screening did not seem to be cost-effective. 62 A recent modelling study, again using Danish data, contradicts that previous conclusion, suggesting that screening men at age 65 years is highly cost-effective compared with no screening and, additionally, that rescreening after 5 years may be a cost-effective extension to the programme.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the concept of its use for screening of at risk populations. In the last 20 years there have been four population based randomised controlled trials which have assessed the value of targeted screening in reducing mortality from abdominal aortic aneurysms in the unselected elderly male population [2][3][4][5] . These trials which have been undertaken in Chichester (England) 2 , England (MASS trial) 3 , Viborg County (Denmark) 4 and the city of Perth and suburbs (Western Australia) 5 have together recruited over 120,000 subjects.…”
Section: Targeted Screening For Aaamentioning
confidence: 99%
“…AAA-related mortality has been shown to decrease by 40 % at 3-5 years [11], and 42-66 % at 13 years [12,13], with an absolute decline in mortality by 1.4 per 1000 men [12]. AAA-mortality at 5-12 years was shown to be 0-2.4 % [5,6], with a 42-52 % decrease of AAA related death in those who attended screening [12,13].…”
mentioning
confidence: 99%
“…All-cause mortality was also shown to be slightly decreased by 3 % at 11-15 years, possibly due to management of other cardiovascular risk factors [1,12]. The incidence of rupture was also significantly reduced (Hazard ratio of 0.44-0.57) up to 13 years [12,13]. The rate of emergency repair was halved and elective repair doubled upto 13-15 years [12,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation